Association between elevated maternal serum MSX1 and IRF6 levels and fetal orofacial clefts: implications for clinical prediction - Cao, Juan (American journal of translational research, 2025)
To investigate the association between maternal serum expression levels of Msh homeobox 1 (MSX1) and interferon regulatory factor 6 (IRF6) and fetal cleft lip and palate (CLP), as well as their potential role in clinical prediction. A prospective case-control study was conducted. A total of 100 pregnant women carrying fetuses diagnosed with CLP via prenatal screening and diagnosis at The Affiliated Women and Children's Hospital of Ningbo University from July 2021 to June 2024 (CLP group) and 105 pregnant women with healthy fetuses (normal group) were selected as the research subjects. Clinical data and relative expression levels of MSX1 and IRF6 were collected. Binary logistic regression was used to analyze the influencing factors of fetal CLP. A Gradient Boosting Machine (GBM) model was developed using R language 4.4.1 software to predict fetal CLP and evaluate its predictive performance. The serum levels of MSX1 and IRF6 in the CLP group were higher than those in the normal group (t = 6.536, 9.907; both P < 0.001). Independent influencing factors for fetal CLP included maternal age, family history of CLP, malnutrition during pregnancy, and expression of MSX1 and IRF6. A GBM model was constructed based on these factors, with their relative importance ranked as follows: IRF6 > MSX1 > family history of CLP > maternal malnutrition > age. In the training set, the GBM model achieved an area under the curve (AUC) of 0.898 (95% CI: 0.849, 0.948), with a sensitivity of 79.2% and specificity of 88.7%. In the validation set, the AUC was 0.895 (95% CI: 0.818, 0.973), with sensitivity of 85.7% and the specificity of 82.4%. The calibration curve demonstrated good agreement between predicted and actual probabilities. Decision curve analysis showed a threshold probability range of 0.30-0.72 in the training set and 0.30-0.73 in the validation set. Elevated maternal serum MSX1 and IRF6 expression levels are closely associated with fetal CLP and may serve as potential biomarkers for its clinical prediction.